2019 IEEE World Haptics Conference (WHC) 2019
DOI: 10.1109/whc.2019.8816133
|View full text |Cite
|
Sign up to set email alerts
|

Command Acknowledge through Tactile Feedback Improves the Usability of an EMG-based Interface for the Frontalis Muscle

Abstract: This work presents a study on the effectiveness of tactile feedback for the acknowledgement of a correct command detection in an EMG-based interface for the frontalis muscle. EMG interfaces are increasingly used in assistive robotics to control robots exploiting the repeatability and robustness of the electromyographic signal. However, in many application a feedback about the correct detection of an input is often missed and the user has to wait for the device motion in order to understand if his/her will has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In the event-driven mode, the occurrence of an event drives the evolution of a finite state machine selecting a motion primitive within a finite set, which in turn defines the reference trajectory for the robot. The event can be triggered by either a physical switch on the interface [55] or by the detection of a posture, gesture or contraction of the human body [39,54,70].…”
Section: Discussionmentioning
confidence: 99%
“…In the event-driven mode, the occurrence of an event drives the evolution of a finite state machine selecting a motion primitive within a finite set, which in turn defines the reference trajectory for the robot. The event can be triggered by either a physical switch on the interface [55] or by the detection of a posture, gesture or contraction of the human body [39,54,70].…”
Section: Discussionmentioning
confidence: 99%
“…The device is designed to recognize the movement of the eyebrows through real-time sEMG measurement of the frontalis muscle ( Hussain et al, 2016 ; Salvietti et al, 2017 ). In Franco et al (2019) , the authors have shown that a vibrotactile feedback at the occipital area of the head can be used as an acknowledgement of the correct processing of the sEMG signal improving the usability of the interface. In this way, whenever the user moves the eyebrows to control the Sixth Finger, the e-Cap informs the user with a short vibration burst that the Sixth Finger is about to close or to open.…”
Section: System Componentsmentioning
confidence: 99%
“…Being an sEMG-based interface, it requires a calibration before operational use. The trigger for the calibration was upgraded in comparison to previous versions ( Hussain et al, 2016 ; Franco et al, 2019 ). The physical switch was replaced by a copper pad that acts as a touch button.…”
Section: System Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SoftPro Wearable System [19] is a wearable technology demonstrator assembled and tested by the University of Siena. It integrates the Assistive Elbow Orthosis (AEOs) from Chapter 2 with a supernumerary robotic nger called the Robotic Sixth Finger [59], a exible surface electromyography (sEMG) interface [74] embedded in a cap called e-Cap [18,26], and a haptic interface called CUFF [6]. The integrated device worn by a healthy subject is shown in 2) 2) e-Cap: f) capacitive touch sensor, g) sEMG electrodes (inside), h) power supply, i) vibrotactile motor, j) signal processing unit; 3) CUFF: k) motor housing, l) encoders and connectors, m) Velcro strap, n) fabric belt…”
Section: Softpro Wearable Systemmentioning
confidence: 99%